Kinerja keuangan sektor perbankan pada masa pandemi COVID-19 - Runa, Yesika; Pontoh, Winston; Korompis, Claudia W.M. (Yayasan Widyantara Nawasena Raharja, 2025)
The WHO announced the discovery of the new strain of the virus at the end of December 2019. COVID-19's impact on the banking sector is undeniable. Ratio analysis is one of many analytical techniques that can be used to calculate bank financial performance. The aim of this research is to identify discrepancies in the financial performance of the banking sector, as measured by the CAMEL method, during the pandemic. This research uses a comparative study with a quantitative approach. The purposive sampling technique was used to collect the sample, and 20 banking company sectors were found to meet the sample selection criteria. This research uses two analytical tools: the Paired Sample T-Test and the Wilcoxon Signed Rank Test. The results of this research definitively show that there is no difference in CAR between 2020 and 2021, 2020 and 2022, and 2020 and 2023. It is clear that there is no difference in NPL between 2020 and 2021, 2020 and 2022. However, there is a difference in NPL between 2020 and 2023. There is a clear difference in ROE between 2020 and 2021, 2020 and 2022, as well as 2020 and 2023. It is clear that there is a difference in ROA between 2020 and 2021, 2020 and 2022, and 2020 and 2023. It is clear that there is no difference in LDR between 2020 and 2021, or between 2020 and 2023. However, there is a clear difference in LDR between 2020 and 2023.